Full predictive cascaded speed and current control of an induction machine - Garcia, Cristian; Rodriguez, Jose; Silva, César Armando; Rojas, Christian; Zanchetta, Pericle; Abu-Rub, Haitham (Institute of Electrical and Electronics Engineers, 2016)
This paper presents and experimentally validates a new control scheme for electrical drive systems, named cascaded predictive speed and current control (PSCC). This new strategy uses the model predictive control concept. It has a cascaded structure like that found in field-oriented control or direct torque control. Therefore the control strategy has two loops, external and internal, both implemented with model predictive control. The external loop controls the speed, while the inner loop controls the stator currents. The inner control loop is based on Finite Control Set Model Predictive Control (FCS-MPC), and the external loop uses MPC deadbeat, making full use of the inner loop‘s highly dynamic response. Experimental results show that the proposed strategy has a performance that is comparable to the classical control strategies but that it is overshoot-free and provides a better time response.